Kajian Kesalehan Sosial Masyarakat Kabupaten Banjar - Mardiana, Mardiana; Sulfihidayatullah, Muh.; Eurotama, Rumbaka Fachrizal; A., Siti Aisyah; Setiadi, Deddy; Najib, M.; Nihlah, Siti Sa’adatin (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the Social Compliance Index (IKS) in Banjar Regency and compare it with the National IKS of 2023. The findings indicate significant differences between the two regions across various dimensions of IKS, which include Social Awareness, Interpersonal Relations, Ethics and Morality, Environmental Conservation, and Compliance with Government Regulations. The Interpersonal Relations dimension in Banjar Regency scored 84.812, higher than the National IKS score of 78.190, indicating that the community in Banjar Regency has better social relationships and a higher level of tolerance. Similarly, in the Compliance with Government Regulations dimension, Banjar Regency scored 88.414, higher than the National IKS score of 86.060, reflecting a higher level of adherence to regulations. However, some dimensions showed a negative gap, such as Social Awareness and Environmental Conservation. Social Awareness in Banjar Regency reached 70.808, significantly lower than the National IKS of 80.410, indicating that social consciousness and empathy towards others still need improvement. Likewise, in Environmental Conservation, Banjar Regency scored 71.249, while the National IKS reached 80.280, showing that environmental awareness in the region still requires more attention. Additionally, the analysis of the relationship between antecedents (Habituation, Ritual Piety, Knowledge, and Exposure to Government Programs) and the IKS of Banjar Regency revealed a fairly strong influence. Habituation had the most significant impact with a value of 0.627, followed by Ritual Piety (0.165) and Knowledge (0.081), while Exposure to Government Programs scored 0.100. These findings indicate that social habits and religious activities play an important role in shaping the social attitudes of the community in Banjar Regency. Overall, although the IKS of Banjar Regency shows some better results compared to the National IKS, there are still major challenges in Social Awareness and Environmental Conservation that need more attention to improve the overall social quality of the community.